Protection of Video Copyrights on the Youtube Platform in Fair Use Principles - Hanson, Nathania Abigail; Permata, Rika Ratna; Ramli, Tasya Safiranita (JURNAL LEGALITAS, 2022)
In copyright, there are two exclusive rights, namely economic and moral rights, and these two rights are not owned by the creator or copyright holder because there is a principle called the Fair Use Principle. Video copyright is one of the objects of copyright protection in digital media whose existence is in great demand by various circles of society because it is easy to access gadgets and internet networks. One of the platforms that are often used to upload, watch, and share videos is Youtube. The specification of this research is Legal Research using a normative juridical approach and data collection techniques utilizing a literature study, then analyzed in a qualitative normative manner. The results of this study are on the Youtube Platform. Several channels re-upload video copyrighted works that do not belong to them without permission, even if those channels do not include the source, and monetization is carried out so that it is for commercial purposes. It is not following Fair Use principles and the Youtube platform as an organizer. The electronic system, of course, also has responsibility for violations that occur on its Platform, which in this case is the occurrence of copyright infringement